Multifarious applications of bioactive glasses in soft tissue engineering - Majumdar S.; Gupta S.; Krishnamurthy S. (My University, 2025)
Tissue engineering (TE), a new paradigm in regenerative medicine, repairs and restores the diseased or damaged tissues and eliminates drawbacks associated with autografts and allografts. In this context, many biomaterials have been developed for regenerating tissues and are considered revolutionary in TE due to their flexibility, biocompatibility, and biodegradability. One such well-documented biomaterial is bioactive glasses (BGs), known for their osteoconductive and osteogenic potential and their abundant orthopedic and dental clinical applications. However, in the last few decades, the soft tissue regenerative potential of BGs has demonstrated great promise. Therefore, this review comprehensively covers the biological application of BGs in the repair and regeneration of tissues outside the skeleton system. BGs promote neovascularization, which is crucial to encourage host tissue integration with the implanted construct, making them suitable biomaterial scaffolds for TE. Moreover, they heal acute and chronic wounds and also have been reported to restore the injured superficial intestinal mucosa, aiding in gastroduodenal regeneration. In addition, BGs promote regeneration of the tissues with minimal renewal capacity like the heart and lungs. Besides, the peripheral nerve and musculoskeletal reparative properties of BGs are also reported. These results show promising soft tissue regenerative potential of BGs under preclinical settings without posing significant adverse effects. Albeit, there is limited bench-to-bedside clinical translation of elucidative research on BGs as they require rigorous pharmacological evaluations using standardized animal models for assessing biomolecular downstream pathways. This journal is © The Royal Society of Chemistry.